Students’ Motivation to Learn English Using Mobile Applications: The Case of Duolingo and Hello English - Tuti Hidayati; Sari Diana (JEELS (Journal of English Education and Linguistics Studies), 2019)
The development of language learning mobile application soft-wares (apps) for smart mobile devices such as smartphones and tablet computer has risen amazingly in these recent days. These apps were continuously reported to be highly potential to support the students to learn the target language. This study introduced two free English learning apps to the students and investigated how they made use of the apps to support their English learning. More specifically, it examined how their English motivation in learning English is, how they used the apps, and whether their different level of motivation influenced the time they spent in accessing the apps. The study was conducted in a mixed method approach utilizing daily journal and questionnaire as the instruments to collect data. The finding pointed that the students were considerably active in using both of the apps. They could enjoy the practicality and flexibility of learning English by the apps despite some superficial engagement. In addition, although students’ English learning motivation was found to have no influence on the amount of time spent in using the apps, their positive response toward using the apps was a potential indication to foster independent English learning outside the classroom. A further detailed finding was discussed along with important issues in the current trends of mobile language learning.